Relationship between Learning Habits and Biology Learning Outcomes among Senior High School Students - Febrina Ramadhani; Muhammad Yunus; Marini Marini (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the relationship and differences between study habits and Biology learning outcomes among high school students based on their academic ability levels. Methodology: This study employed a quantitative correlational design. The sample consisted of 152 students selected through proportionate stratified random sampling. Data on learning habits were collected using a four-point Likert-scale questionnaire comprising 38 valid items, while Biology learning outcomes were obtained from students’ academic records. Data were analyzed using descriptive statistics, Pearson Product Moment correlation, significance testing, and coefficient of determination analysis. Main Findings: Most students had learning styles in the excellent category (97.37%), but the majority of Biology learning outcomes were in the low category (70.40%). The relationship between learning styles and Biology learning outcomes was not significant in the high academic ability group (r = 0.126), but was significant in the medium (r = 0.255) and low (r = 0.490) academic ability groups. The contribution of learning styles to learning outcomes increased from 1.59% in the high academic ability group to 24.01% in the low academic ability group. Novelty/Originality of this study: This study contributes new insights by examining the relationship between learning habits and Biology learning outcomes across different academic ability levels. The findings reveal that the strength and significance of the relationship vary according to students’ academic ability, providing a more specific understanding of the role of learning habits in supporting Biology learning achievement.